2011
DOI: 10.1016/j.ajhg.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Microcephaly with Simplified Gyration, Epilepsy, and Infantile Diabetes Linked to Inappropriate Apoptosis of Neural Progenitors

Abstract: We describe a syndrome of primary microcephaly with simplified gyral pattern in combination with severe infantile epileptic encephalopathy and early-onset permanent diabetes in two unrelated consanguineous families with at least three affected children. Linkage analysis revealed a region on chromosome 18 with a significant LOD score of 4.3. In this area, two homozygous nonconserved missense mutations in immediate early response 3 interacting protein 1 (IER3IP1) were found in patients from both families. IER3IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 42 publications
2
84
0
1
Order By: Relevance
“…Under the DTT condition, we know that normal cells slightly increase susceptibility to apoptosis from 10 to 18% (Figure 4c and Supplementary Figure S5). 27 No clear signs of ER stress were detected by KDEL staining under DTT in the patient cells (Supplementary Figure S4). 24 We then tested whether signs of expression of ER stress markers could be detected by western blot analysis using antibodies specific for IRE1, cleaved form of ATF6, CHOP, BiP and by real time-PCR for XBP-1 splicing.…”
Section: Er Stress Response and Apoptosismentioning
confidence: 98%
See 1 more Smart Citation
“…Under the DTT condition, we know that normal cells slightly increase susceptibility to apoptosis from 10 to 18% (Figure 4c and Supplementary Figure S5). 27 No clear signs of ER stress were detected by KDEL staining under DTT in the patient cells (Supplementary Figure S4). 24 We then tested whether signs of expression of ER stress markers could be detected by western blot analysis using antibodies specific for IRE1, cleaved form of ATF6, CHOP, BiP and by real time-PCR for XBP-1 splicing.…”
Section: Er Stress Response and Apoptosismentioning
confidence: 98%
“…32 Some of the COL4A2 patients are born microcephalic and the reason is not apparent at the moment, but it could be related to susceptibility of the developing brain to apoptosis. 27 It is also possible that, independently of the ER stress, COL4A2 and the apoptotic pathways are linked as they are developmentally co-regulated. In fact, it has been shown that micro RNA mir-29b represses expression of both COL4A2 and antiapoptotic Bcl-2 family member Mcl-1 during skeletal development.…”
Section: Pathogenesis Of Col4a2 Mutationsmentioning
confidence: 99%
“…More data are available for full trisomy 18: These dosage imbalances might, for some neuronal genes, lay the basis for the observed epilepsy phenotypes. Among these, some genes are of special interest as they could be implicated in epilepsy pathogenesis: SYP4 that encodes synaptogamin 4, a protein with a crucial role in synaptic transmission [37] ; IER3IP1, which codifies immediate early response 3 interacting protein 1 and is mutated in patients with myoclonic epilepsy [21] ; MBD1 and MBD2, that codify methylCpG binding domain protein 1 and 2, nuclear proteins with a methyl-CpG binding domain [38] ;…”
Section: Discussionmentioning
confidence: 99%
“…Brain MRI showed a simplified gyral pattern of the cerebral cortex and delayed myelination. Epilepsy was drug-resistant despite the treatment with clonazepam, vigabatrin and valproic acid [21] .…”
Section: P-deletion Syndromementioning
confidence: 99%
“…Postnatal apoptosis has a significant influence on brain growth (Kuan et al 2000;Polster et al 2003;Madden et al 2007), including regulating neuronal density (Sanno et al 2010), and apoptotic genes may have been targeted by selection in relation to primate brain expansion (Vallender and Lahn 2006). Disruption of apoptosis causes microcephaly (Poulton et al 2011), potentially explaining the association between DUF1220 dosage and head circumference (Dumas et al 2012). The association of NF-kB with inflammatory diseases (Tak et al 2001) is also intriguing, given the growing evidence that the inflammatory response is linked to the risk and severity of ASD (Meyer et al 2011;Depino 2012).…”
Section: Discussionmentioning
confidence: 99%